Two Phase Assessment of Vortex-Structure and Heat Transfer for Immiscible Fluids in Curved Channel - Nadim, Nima; Chandratilleke, Tilak; Narayanaswamy, Ramesh (AHMTC Monash University, 2011)
Multi-phase, turbulent, incompressible and immiscible fluid with different viscous and thermal properties has been numerically investigated in curved channel. The Mixture model which is a simplified two-phase flow model has been used while k-ω model is designated as a turbulence closure. The concept of dimensionless helicity and entropy generation have been modified for current case and used for post-processing purposes. Effect of interaction between centrifugal force and gravity has been investigated in terms of phase mapping and vortex instruction for different orientation and flow rate. Phase re-arrangement procedure throughout the curved part first is investigated and this base is used to discus following effects. Separation of phases due to centrifugal force which means separated fluids with different viscosity causes a new approach for inception of Dean instability which significantly changes heat transfer as well.